Larotrectinib treatment for infantile fibrosarcoma in newborns: a case report and literature review - Wang, Dandan; Zhang, Fanhui; Feng, Wanli; Pan, Jiarong; Yuan, Tianming (Frontiers in Oncology, 2023)
Infantile fibrosarcoma (IFS) is a rare tumor in childhood characterized by a single, localized, painless mass that grows rapidly but has a relatively indolent biological behavior and a favorable prognosis.Eighty-five percent of infantile fibrosarcomas are associated with t (12;15) (p13;25) chromosomal translocation resulting in ETV6-NTRK3 gene fusion, which provides the target for targeted therapy.Here, we report a case of IFS in a newborn with a mass in the left lower extremity confirmed by imaging, histopathological examination, tissue FISH testing, and high-throughput sequencing to detect gene rearrangement. Based on gene fusion targeted drug testing results, the patient was treated with standard doses of larotrectinib, resulting in significant mass shrinkage with no adverse effects, demonstrating the treatment effect of targeted therapy. This case provides a reference for using larotrectinib in newborns with IFS.